BerlInversions. Issue 2 (1st June 2020) - Smith, Murray
Abstract: Todd Berliner's Hollywood Aesthetic advances an original perspective on Hollywood filmmaking by insisting on its fundamentally aesthetic character, and exploring its particular aesthetic features with the tools of neoformalist film analysis, cognitive psychology, and the philosophy of art. I focus on two of the book's most ambitious claims: a) that appreciation of the style of Hollywood films can play an important role in our experience of them, over and above its role in representing and expressively dramatizing narrative elements; and b) that the ideological dimension of Hollywood filmmaking serves its aesthetic purposes, rather than vice versa. I conclude by noting a common root to the resistance likely to greet Berliner's two bold inversions of conventional wisdom on narrative, style, aesthetics, and ideology.